Plasma waves as a benchmark problem. (February 2017) - Kilian, Patrick; Muñoz, Patricio A.; Schreiner, Cedric; Spanier, Felix
Abstract : A large number of wave modes exist in a magnetized plasma. Their properties are determined by the interaction of particles and waves. In a simulation code, the correct treatment of field quantities and particle behaviour is essential to correctly reproduce the wave properties. Consequently, plasma waves provide test problems that cover a large fraction of the simulation code. The large number of possible wave modes and the freedom to choose parameters make the selection of test problems time consuming and comparison between different codes difficult. This paper therefore aims to provide a selection of test problems, based on different wave modes and with well-defined parameter values, that is accessible to a large number of simulation codes to allow for easy benchmarking and cross-validation. Example results are provided for a number of plasma models. For all plasma models and wave modes that are used in the test problems, a mathematical description is provided to clarify notation and avoid possible misunderstanding in naming.